Interdependence, asymmetric crises, and European defence cooperation. Issue 2 (3rd April 2017) - Haroche, Pierre
ABSTRACT: Although international crises are often believed to represent windows of opportunity to strengthen European defence cooperation, recent crises have not seemed to produce a clear convergence of European Union (EU) member states' security interests. This article seeks to address this puzzle by arguing that European defence cooperation is a response to crises that place European states in a situation of military interdependence. Conversely, asymmetric crises, i.e. crises that affect European states unevenly, encourage those states to maintain their autonomy of action. This theoretical argument is supported by two case studies: the failure of the European Defence Community in the early 1950s and the current difficulties experienced by the EU's military operations. These two cases illustrate a striking continuity in that, because of (neo)colonial ties in particular, European states are often unevenly affected by international crises, which tends to make defence cooperation less effective.